Energy Focusing Efficiency Estimation of a Multi-Level Fresnel Lens Through Surface Profile - Bui, Tuan-Anh (Old Journal, 2018)
A high focusing efficiency of a multi-level Fresnel lens is desired when it is designed and manufactured. How to determine the focusing efficiency becomes a problem after the Fresnel lens is fabricated. A method to estimate the focusing efficiency of the Fresnel lens basing on its surface profile is proposed. Hence, the profile of Fresnel lens fabricated shows how similar with the profile designed, which has been theoretically predicted a maximal focusing efficiency such as 40.5% and 81% for a two-phase and four-phase level Fresnel lenses, respectively. This calculation method can be applied to estimate the focusing efficiency of any surface profile of Fresnel lenses fabricated without a direct measurement of focusing efficiency. The focusing efficiency of a four-phase level Fresnel lens designed to operate at a frequency of 100 MHz of an ultrasonic ejector, which was fabricated by a two-mask process using SU-8 photoresist, approximate 60% is illustrated.